Purification and characterization of PAP phytase from Indian wheat variety DBW 17 - Verma, Anukriti; Ram, Sewa; Dalal, Sunita (Journal of Cereal Research, 2011)
Phytase (myo-inositol hexakisphosphate phosphohydrolase E.C.3.1.3.8) was isolated and purified from Indian wheat variety DBW 17 using 5-step purification procedure as (NH4)2SO4 fractionation, cold methanol fractionation, DEAETrisacryl M chromatography, Ultrogel AcA34 filtration chromatography and SP-Trisacryl M chromatography. Two forms of the enzyme as PHY1 (64 kDa) and PHY2 (62 kDa) were identified. There was 79.0 fold purification of PHY1 and 114.8 fold of PHY2. The optimum pH for PHY1 and PHY2 was 6.0 and 5.5 respectively while optimum temperature 55Â°C for both the isozymes. The Km value for the hydrolysis of phytate was 123 ÂµM for both the isozymes indicating high specificity for phytate. Wheat phytase can be used in hydrolysis of phytate in food industries for releasing micronutrients and hence increasing their bioavailability